'Whatever you say, say nothing': Teaching public administration in Northern Ireland. Issue 1 (March 2019) - Knox, Colin
This article is a contribution to a special issue of Teaching Public Administration, which offers teachers with many years' experience the opportunity to reflect on changes over time. The context for this paper is teaching public administration in Northern Ireland, a region of the UK that has a sizeable public sector but a distinctive and unstable structure of governance. The paper begins by summarizing the pedagogic polemic in teaching public administration, how this played out in a devolved region of the UK that has witnessed political conflict, and the influence of this setting on the provision of higher education for public sector officials. It addresses how a regional university has sought to meet the seemingly parochial demands of its students with the wider demands for global outward-facing teaching and research.